Quantum Reality, Relativistic Causality, and Closing the Epistemic Circle : essays in honour of abner shimony - Myrvold, Wayne C. (Springer, 2017)
Philosophy, Methodology and History -- Bell’s Theorem and Nonlocality -- Probability, Uncertainty, and Stochastic Modifications of Quantum Mechanics...